PHOS PHATE TREATMENT OF FROZEN PRAWNS II. FROZEN STORAGE CHARACTERISTICS OF PRAWN MEAT TREATED WITH POLY PHOSPHATES - MATHEN, CYRIAC (Fishery Technology, 2025)
This communication reports the changes in physical, organa= Jeptic and biochemical characteristics of prawn meat dip-treated with alkaline and neutral solutions of polyphosphates during frozen storage. Results are presented on changes in thawed and cooked yields, Water extractable nitrogen, non-protein nitrogen, free cx:amino nitrogen, salt solubility, myosin and moisture in the muscle and loss of soluble nitrogenous constituents in thaw drip during frozen storage upto seven months. The salt solubility remained unchanged during storage in samples treated with neutral polyphosphate solutions and the organoleptic quality was superior to control sample. It is concluded that dip treatment with neutralised solutions of tripolyphosphate not only maintains correct drained weight and improves cooked yield during prolonged frozen storage but also protects the frozen product from denaturation as measured by the salt solubility of the proteins. INTRODUCTION